Many or too many progesterone membrane receptors?: clinical implications - Wendler, Alexandra; Wehling, Martin (Trends in endocrinology and metabolism, 2022)
Several receptors for nongenomically initiated actions of progesterone (P4) exist, namely membrane-associated P4 receptors (MAPRs), membrane progestin receptors (mPRs), receptors for neurosteroids [GABAA receptor (GABAAR), NMDA receptor, sigma-1 and -2 receptors (S1R/S2R)], the classical genomic P4 receptor (PGR), and α/β hydrolase domain-containing protein 2 (ABHD2). Two drugs related to this field have been approved: brexanolone (Zulresso™) for the treatment of postpartum depression, and ganaxolone (Ztalmy™) for the treatment of CDKL5 deficiency disorder. Both are derivatives of P4 and target the GABAAR. Several other indications are in clinical testing. CT1812 (Elayta™) is also being tested for the treatment of Alzheimer’s disease (AD) in Phase 2 clinical trials, targeting the P4 receptor membrane component 1 (PGRMC1)/S2R complex. In this Review, we highlight emerging knowledge on the mechanisms of nongenomically initiated actions of P4 and its derivatives.